Relationship between type 1 diabetes and autoimmune diseases in european populations: A two-sample Mendelian randomization study - Xie, Weidong; Jiang, Haojie; Chen, Yao; Yu, Zhaojie; Song, Yaoyu; Zhang, Huanhao; Li, Sen; Han, Shaoliang; Liu, Naxin (Frontiers in Genetics, 2024)
Background: Previous studies have suggested an association between Type 1 diabetes (T1D) and autoimmune diseases (AIDs), but the causal relationship remains unclear.Therefore, this study utilizes publicly available Genome-Wide Association Studies (GWAS) databases and employs a two-sample Mendelian Randomization (MR) approach to explore the causal relationships between T1D and systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and inflammatory bowel disease (IBD).Methods: Summary GWAS data for T1D, SLE, RA, and IBD were downloaded from open GWAS databases and the International Inflammatory Bowel Disease Genetics Consortium (IIBDGC). We employed a series of methods to select instrumental variables closely related to T1D. To enhance the reliability of our conclusions, we applied multiple robust analytical methods, with the inverse variance weighted (IVW) method as the primary approach. Validation and meta-analysis were conducted using the FinnGen consortium. Additionally, we assessed heterogeneity, pleiotropy, and sensitivity to ensure the robustness of our conclusions.Results: A potential causal association was found between T1D and SLE (OR = 1.37, 95% CI = 1.26-1.49, P < 0.001), which was further confirmed by meta-analysis. Similarly, a potential causal association was found between T1D and RA (OR = 1.32, 95% CI = 1.17-1.50, P < 0.001), and this was also confirmed by meta-analysis. Although the association between T1D and IBD showed P < 0.05, the leave-one-out test did not pass, and further meta-analysis indicated no significant statistical association between them.Our study reveals the relationships between T1D and three clinically common autoimmune diseases (SLE, RA, and IBD). This research supplements previous studies and provides a reference for future clinical work